The Social Role of Religion in Feudal Society - Gendrolis, Edmundas (Problemos, 1968)
The whole history of the Middle Ages, as F. Engels points out, had no other form of ideology except religion and theology. Despite estate differences determining the rights and duties of the members of feudal society, Christianity proclaimed equality of all people before God, since all people obey him. Life on earth became only a preparation for the “real” life in heaven. God was considered the main prop of the existing order. In this connection the article analyses the views of the representatives of the feudal Catholic Church such as Augustine, P. Abelard, Thomas Aquinas and others on the social principles of Christianity and religious tolerance in particular. The Catholic Church, considering itself the body of God, sanctioned the feudal relations of production as given by God. Political, legal and philosophical problems were to be solved only on the theological basis. The dogmas of religion were compulsory for everybody, no individual interpretation being allowed. Another understanding or interpreting of these dogmas was treated as an attempt, direct or indirect, on the social system and the Church. The punishment of those advocating different ideas – heretics, and the measures of violence against people of different religion acquired the meaning of saving their souls. In the society where the only form of ideology was religion, religious tolerance was utterly impossible. Any social political movement always took a religious colouring. These factors determined a particular place of religion in the society and the attitude ol man and state towards it.